2005
DOI: 10.3928/1081-597x-20050901-19
|View full text |Cite
|
Sign up to set email alerts
|

Topography-guided Custom Retreatments in 27 Symptomatic Eyes

Abstract: PURPOSE: To evaluate the use of topography-guided ablations for refractive irregularities induced by previous surgery. METHODS: This prospective, non-comparative trial comprised 27 symptomatic eyes with a history of LASIK for myopia that underwent topography-guided treatment with the ALLEGRETTO WAVE system. Pre- and postoperative refraction, uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), corneal asphericity (Q value), low contrast sensitivity, and patient's subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…With this method, aberrated eyes such as small optical zones, decentered optical zones, and irregular astigmatic corneas may be treated with improved predictability over our previous unpublished experience with topography-guided ablations when our results were similar to those reported by others. 13,14 In our study, we have shown the fi nal refraction to be within 1.00 D of intended in 94% of eyes with both decentered and small optical zone retreatments, with more than 75% of these being within 0.50 D. Although these numbers could be improved with further refi nement, the complexity of these cases should not be underestimated. Rather these outcomes would likely rival the best predictability of complex wavefront-guided retreatments, especially without a well accepted nomogram or strategic approach.…”
Section: S444mentioning
confidence: 53%
See 1 more Smart Citation
“…With this method, aberrated eyes such as small optical zones, decentered optical zones, and irregular astigmatic corneas may be treated with improved predictability over our previous unpublished experience with topography-guided ablations when our results were similar to those reported by others. 13,14 In our study, we have shown the fi nal refraction to be within 1.00 D of intended in 94% of eyes with both decentered and small optical zone retreatments, with more than 75% of these being within 0.50 D. Although these numbers could be improved with further refi nement, the complexity of these cases should not be underestimated. Rather these outcomes would likely rival the best predictability of complex wavefront-guided retreatments, especially without a well accepted nomogram or strategic approach.…”
Section: S444mentioning
confidence: 53%
“…Topography-guided Ablation in Highly Aberrated Eyes/Lin et al outcome is most criticized, although a recent resurgence in topography-guided retreatments with the WaveLight ALLEGRETTO laser and Topolyzer suggests that this limitation can be overcome. 13,14 Previous studies in symptomatic eyes following refractive surgery have reported an improvement of BSCVA from a mean of 20/32 preoperatively to 20/21 postoperatively. 14 Despite this improvement, the refractive outcome may be less predictable due to the unknown spherical component of the correction that changes the refraction postoperatively.…”
Section: S444mentioning
confidence: 99%
“…Induction of HOAs, especially coma, is a key contributor to symptoms after LRS in humans. 1,[12][13][14]17,34,35 We noted that the induction of HOAs by decentration occurred in an irregular pattern that may have resulted from treatment-induced, nonrotationally symmetric aberrations. There was also a large difference in the induction of coma at 3.5-and 6-mm PDs.…”
Section: Hoa and Best-corrected Optical Qualitymentioning
confidence: 99%
“…Besides causing severe deterioration of visual quality, such complications are difficult to treat, and success is often limited. [12][13][14][15][16][17][18] Although several studies on decentration-induced aberrations after conventional 1,2,7 and wavefront-guided LRS 3,4,8,19 have been published, all assumed a perfect ablation and did not consider the inherent induction of HOA which occurs in real corneas as a result of wound healing and biomechanical effects. 20,21 The present study was conducted to investigate the effects of decentration of the laser ablation relative to the entrance pupil of the eye on LOA, HOA, and optical quality, in a cat photorefractive keratectomy (PRK) model.…”
mentioning
confidence: 99%
“…This group of cases may be better addressed with the use of topography-guided enhancements as reported by the authors previously. 14 We did not study the specifi c correction of each Zernike polynomial in these wavefront-guided enhancements, but the total high order deviation through the value of RMSH was evaluated. One may theorize that applying wavefront-guided treatments as an initial treatment may provide better results.…”
Section: Discussionmentioning
confidence: 99%